Screening for Salt Tolerance in Chenopodium quinoa Genotype Seedlings through Germination in a Hydroponic System - Jaikishun, Sirpaul; Song, Shikui; Yang, Zhenbiao (Journal of Applied Life Sciences International, 2023)
Quinoa (Chenopodium quinoa Willd.) is poised to be a global life changer with its ability to adapt to a wide range of abiotic stresses and as a highly nutritious and sustainable food source. A trial on screening of salt tolerance was conducted at the germination and seedling stages of 69 quinoa genotypes in different concentrations of NaCl 0 (CK), 100, 200, 300, 400, and 500 mM for 21 days in the MS/2 mixture. This results in 16 genotypes with >50% germination at 400 mM NaCl. These were reassessed in germination indices and relative growth. Results indicated that Chadmo had the highest germinability of 97% and 32.76% relative height among the 16 genotypes.  Considering the germination indices, Chadmo had significantly different values (3.05±0.19 day-1) in mean germination time, coefficient of variation of the germination time (38.76±1.97%), the velocity of germination (0.23±0.01 day-1), the uncertainty of germination (0.54±0.08 bit), synchrony of germination (0.42±0.05 and Timson’s index (48.89) with significant differences (P<0.05) among the genotypes.  Moreover, Chadmo had the highest membrane stability index (MSI) (60.03±11.84) at 400 mM NaCl and the least relative change between the CK and 400 mM NaCl with 30.87±2.01%. Assessing the stress inhibitory effect of the 16 genotypes, Chadmo had the least relative difference between the CK and 400 mM NaCl with shoot length of 34.34%, root length of 25.57%, fresh weight of 22.05%, dry weight of 3.62% and moisture content of 1.99% with Tukey analyses identifying significant differences (p<0.05). To select the salt-sensitive genotype, an assessment was done on five genotypes that exhibited the least germination at 200 mM NaCl. Kankolla had the least germinability with 12 and 4% at 100 and 200 mM NaCl, respectively. Considering all these parameters, Chadmo and Kankolla were selected as salt-tolerant and salt-sensitive for further analyses.